Exploitation of Indigenous Wine Yeasts from Spontaneously Fermenting Grape must and Vineyard Soil in Beijing, China - Qianwen Zhang; Hui Li; Xiangyu Sun; Weidong Huang; Jicheng Zhan (eFood, 2020)
The investigation of indigenous wine yeast can facilitate the production of distinctive Beijing wine by providing wineries with more choices in distinctive wine yeasts. Wine yeasts that were isolated from grape must during spontaneous fermentation and from vineyard soil were preliminarily classified by their colony morphologies when cultured on Wallerstein Laboratory Nutrient (WLN) medium and then were identified by 5.8S ITS sequence analysis. Four selected strains were involved in inoculated fermentation tests. The results showed that five yeast species were isolated from the grape must, and five non-Saccharomyces yeast species were found in vineyard soil. The colony morphology of Pichia occidentalis on the WLN medium was described herein for the first time. An effective way which could be used for isolate and select wine yeasts from soil samples on WLN medium was described. And one of the selected indigenous strains shared over 99% similarity on 5.8S ITS sequence with commercial wine yeast, which indicated that commercial yeast might have influenced the local yeast diversity. The two selected indigenous Saccharomyces cerevisiae strains, which showed good fermentation performances, could be applied in the local wine industry in the future.